Effect of Blood Vessels on Measurement of Nodule Volume in a Chest Phantom1 - Ko, Jane P. (2006)
PURPOSE: To identify, by using a chest phantom, whether vessels that contact lung nodules measuring less than 5 mm in diameter will affect nodule volume assessment. MATERIALS AND METHODS: Forty synthetic nodules (20 with ground-glass attenuation and 20 with solid attenuation) that measured less than 5 mm in diameter were placed into a chest phantom either adjacent to (n = 30) or isolated from (n = 10) synthetic vessels. Nodules were imaged by using low-dose (20 mAs) and diagnostic (120 mAs) multi–detector row computed tomography (CT). Nodules that were known to lie in direct contact with vessels were confirmed by visual inspection. Nontargeted 1.25 × 1.00-mm sections were analyzed with a three-dimensional computer-assisted method for measuring nodule volume. A mixed-model analysis of variance was used to examine the influence of several factors (eg, the presence of adjacent vessels; tube current–time product; and nodule attenuation, diameter, and location) on measurement error. RESULTS: The mean absolute error (MAE) for all nodules adjacent to vessels was 2.3 mm(3), which was higher than the MAE for isolated nodules (1.9 mm(3)) (P <.001). This difference proved significant only for diagnostic CT (2.2 mm(3) for nodules adjacent to vessels vs 1.3 mm(3) for nodules isolated from vessels) (P <.05). A larger MAE was noted for nodules with ground-glass attenuation (2.3 mm(3)) versus those with solid attenuation (2.0 mm(3)), for increasing nodule volume (1.66 mm(3) for nodules smaller than 20 mm(3) vs 2.83 mm(3) for nodules larger than 40 mm(3)), and for posterior nodule location (P <.05). CONCLUSION: The presence of a vessel led to a small yet significant increase in volume error on diagnostic-quality images. This represents less than one-third of the overall error, even for nodules larger than 40 mm(3) or approximately 4 mm in diameter. This increase, however, may be more important for smaller nodules with errors of less than 3 mm(3).